A Nomogram for Prediction of Postoperative Pneumonia Risk in Elderly Hip Fracture Patients - Xiang G; Dong X; Xu T; Feng Y; He Z; Ke C; Xiao J; Weng YM (Dove Medical Press, 2020)
Guangheng Xiang,1,2,* Xiaoyu Dong,1,* Tao Xu,1 Yongzeng Feng,1 Zili He,1 Chenrong Ke,1 Jian Xiao,1,2 Yi-Min Weng1 1Department of Orthopaedic, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang 325035, People’s Republic of China; 2School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang 325035, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Xiao; Yi-Min WengDepartment of Orthopaedic, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang 325035, People’s Republic of ChinaEmail xfxj2000@126.com; wzykdxwym@163.comPurpose: Pneumonia is one of the common complications of hip fracture. This study aimed to evaluate the risk factors and apply a nomogram to predict postoperative pneumonia in elderly hip fracture patients.Materials and Methods: From August 2014 to October 2019, 1113 hip fracture patients who were older than 65 years and underwent surgical treatment in our hospital were subjects of this study. Univariate and multivariate Cox analyses were used to identify independent risk factors. A predictive nomogram model was built, and the discrimination and calibration were determined by receiver operating characteristic and calibration plot.Results: A total of 166 patients developed pneumonia after operation (14.91%, pneumonia group) while the remaining 947 patients did not (85.09%, non-pneumonia group). According to the results, body mass index (OR, 0.76, 95% CI, 0.70 to 0.84, P< 0.001), serum albumin (OR, 0.86, 95% CI, 0.79 to 0.93, P< 0.001), c-reactive protein (OR, 1.01, 95% CI, 1.00 to 1.92, P=0.011), functional status (OR, 2.94, 95% CI, 1.69 to 5.10, P< 0.001) and time to surgery (OR, 4.56, 95% CI, 2.64 to 7.88, P< 0.001) were identified as independent risk factors of pneumonia. The area under the curve value for postoperative pneumonia risk was 0.905, and the P-value of the Hosmer-Lemeshow calibration test was 0.529.Conclusion: Our nomogram model can be used to predict the risk of pneumonia in elderly hip fractures after surgery and provide clinicians with guidance for better perioperative intervention to improve prognosis and reduce mortality.Keywords: pneumonia, elderly, hip fracture, risk factors, nomogram